Identification of a novel, dominant dwarfing gene (Ddw4) and its effect on morphological traits of rye. - Zuzanna Kantarek; Piotr Masojć; Anna Bienias; Paweł Milczarski (PLoS ONE, 2018)
Shortening rye stems to improve lodging resistance is among the major tasks awaiting breeders of this cereal. The most straightforward way to achieve this goal is the implementation of a dominant dwarfing gene into high yielding cultivars. The choice of dominant dwarfing genes in rye is limited to Ddw1 and Ddw3 loci, which are well characterized with respect to map position and tightly linked molecular markers on the long arms of chromosomes 5RL and 1RL, respectively. This paper reports on the identification and preliminary characterization of a novel dominant dwarfing gene, Ddw4, from line S44. This was mapped within the centromeric region of chromosome 3R. The Ddw4 gene is sensitive to exogenous gibberellin. Its introduction into the rye populational cultivar Dańkowskie Amber decreased plant height by c. 54% without any negative effects on spike length and number of kernels per spike. Further genetic studies are needed to determine the perspectives for application of the newly detected dwarfing gene into breeding programs for short-stem rye.